Examination of motivation in civic organizations - Pierog, Anita (Acta Agraria Debreceniensis, 2013)
The primary objective of my research is to examine and explore the specialties of the civil organizations composition and operation. In my study I describe the results of my research in Hajdú-Bihar County. The results concern to the features of motivation and incentive in civil organizations. Quantitative data from an empirical analysis is used for the research. My questionnaires were measured on a representative sample. The basis of this sample was the County Court of Justice’s website. Thus, my research on managerial tasks included in Hajdú-Bihar County. During the survey I examined the motivation from different sides. First of all, what was the purpose of establishing civil organizations? I also analysed the managers’ motivation. Why they participate in civic activities? Finally, I examined the perception of managers of incentive forms. The general findings beyond the context of the investigations were carried out on the basis of organizational parameters and characteristics of the interviewees. The results of my research arise from an analysis of data I collected. Civil organizations are established for a well-defined task or as a way of problem-solving. In terms of internal motivation of managers stated that it was mainly an internal urge and desire to help the cause, participate in the activities of civic organizations. In their motivational activities, the psychological incentives were classified as most effective motivators.